Clinical and Haematological Profile of Dengue during 2021 Epidemic at a Tertiary Care Centre, Western Uttar Pradesh, India: A Cross-sectional Study - Payal Mittal; Shehraz Firoz; Neetipriya Pandey; Digvijay Ghangas; Sonia Bhatt (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Incidence of dengue fever has significantly increased in the last few years in developing countries. Its clinical presentation may be variable in paediatrics with high- risk of complications. Dengue fever causes high mortality and morbidity in the paediatric age group. Aim: To evaluate the clinical features and haematological parameters of dengue in paediatric cases in a tertiary care hospital. Materials and Methods: A cross-sectional observational study was conducted in the Department of Paediatrics, FH Medical College, Agra, Uttar Pradesh, India, on patients diagnosed with dengue fever from August 2021 to November 2021. All cases were subjected to detailed clinical history, examination and relevant investigations (laboratory parameters and clinical features). Data was collected in predesigned proforma, entered in Microsoft Excel sheet and analysed. Results: Out of 801 patients, 486 (60.67%) were males and 315 (39.33%) were females. The commonest symptoms were fever (n=779, 97.25%) followed by body pain/ arthralgia (n=700, 87.39%), flushing (n=622, 77.65%), abdominal pain (n=437, 54.55%), and vomiting (n=428, 53.43%). Highest number of cases (n=399, 49.82%), were from dengue with warning signs. Of total, 759 (94.75%) cases had thrombocytopaenia. Common complications were pleural effusion (26.8%) and ascites (11.88%). Of total, 611 (76.27%) cases got cured while 81 (10.11%) patients expired. Conclusion: Dengue fever is more common in paediatric age group with high rate of complications and disease severity, which has high mortality rate. High clinical suspicion and early fluid management are the only measures to reduce the mortality and morbidity.